Effects of varying wheat levels on growth performance, intestinal barrier, and cecal microbiota of broilers - Wang, Leilei; Wei, Bin; Si, Xuemeng; Huang, Yanqun; Zhang, Huaiyong; Chen, Wen (Frontiers in Veterinary Science, 2024)
The study aimed to investigate the potential effects of varying wheat levels in broiler diets on growth performance, intestinal barrier, and cecal microbiota. Day-old male broilers were fed the same diet until 10 d of age. Then they were randomly assigned to 1) the low-level wheat group, where inclusion of 15.0% and 25.0% wheat in the grower and finisher diet, respectively, 2) the medium-level wheat group with 30.0% and 40.0% of wheat in the grower and finisher periods; and 3) the high-level wheat dietary group, in which the grower and finisher diets contained 55.77% and 62.38% of wheat, respectively. Dietary treatments unaffected the body weight at 39 d, whereas incorporating high wheat in diets significantly increased the feed intake and reduced the feed conversion ratio from 10 to 39 d (P < 0.05). Except for increased phosphorus digestibility in the high wheat group, dietary treatments had no significant effect on the apparent digestibility of dry matter, crude protein, and ether extract. Meanwhile, the broilers that consumed the medium and high content of wheat presented a higher villus height and the ratio of villus height to crypt depth than those fed the low-level wheat birds. Feeding the medium-level wheat enhanced ileal integrity and depressed the expression of proinflammatory cytokines in the ileum. The addition of high levels of wheat reduced the Chao1 index and the abundance of Lactobacillaceae, Bacteroidaceae, and Ruminococcacea in cecal content, which probably decreased the metabolism of histidine, sulfur-containing amino acids, and the biosynthesis of lysine. Collectively, the medium-level wheat diet improved intestinal barrier function and had no deleterious effects on the growth performance of broiler; dietary inclusion of high wheat reduced the feed conversion rate, which might be associated with the disturbed gut microbiota and decreased metabolism of amino acids.